2020
DOI: 10.1177/2156759x20973643
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Secondary Exposure to Trauma and Professional Quality of Life of School Counselors

Abstract: This quasi-experimental study examined secondary exposure to trauma and factors of professional quality of life among a national sample of 361 school counselors. Results indicate that major upheaval between parents, death of a close friend or family member, and emotional abuse are the most common traumatic events that school counselors are exposed to and that school counselors in Title I schools report significantly more exposure. Hierarchical multiple regression results revealed that secondary exposure to tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 45 publications
(64 reference statements)
0
7
0
Order By: Relevance
“…School counselors often carry large caseloads (Mullen et al, 2021) and experience significant stressors on the job (Bledsoe et al, 2021). For example, the majority of school counselors will work with students who have experienced traumas on a daily basis, which can lead to lower professional quality of life (Rumsey et al, 2020). Another factor is the percentage of economically disadvantaged students; this was related to secondary traumatic stress of school counselors (Rumsey et al, 2020).…”
Section: Organizational Predictors Of Wellnessmentioning
confidence: 99%
See 2 more Smart Citations
“…School counselors often carry large caseloads (Mullen et al, 2021) and experience significant stressors on the job (Bledsoe et al, 2021). For example, the majority of school counselors will work with students who have experienced traumas on a daily basis, which can lead to lower professional quality of life (Rumsey et al, 2020). Another factor is the percentage of economically disadvantaged students; this was related to secondary traumatic stress of school counselors (Rumsey et al, 2020).…”
Section: Organizational Predictors Of Wellnessmentioning
confidence: 99%
“…School counselors are expected to engage in wellness practices and this is included in the ASCA Ethical Standards for School Counselors (ASCA, 2016). Given the factors that may interfere with wellness due to organizational systems (Lemmons & Zanskas, 2019) and exposure to numerous stressors (Rumsey et al, 2020), school counselors' awareness of what affects their wellness is important. Encouragingly, several researchers reported that counseling professionals (Lawson & Myers, 2011), including school counselors (Randick et al, 2019), scored higher on the FFWEL when compared to the norming sample of the scale (Hattie et al, 2004).…”
Section: The Indivisible Selfmentioning
confidence: 99%
See 1 more Smart Citation
“…Mason and colleagues 6 specifically spoke of providing collaborative training for school counselors in training to work with school nurses. They mentioned that school counselors in training “in clinical placements can partner with school nurses to provide staff training on mental and physical health issues that disproportionately impact students and families of color.” 6 (p11) Through collaboration, school nurses and school counselors are further able to implement strategies and policies to support students who have experienced trauma such as but not limited to the COVID-19 pandemic, race-based trauma, natural disasters, abuse, parental incarceration, hate crimes, and foster care 24,25 …”
Section: Discussionmentioning
confidence: 99%
“…These terms refer to the powerful emotions and behaviors a person experiences due to empathizing, assisting, or desiring to aid another person significantly affected by a traumatic experience (Figley, 1995). Coupled with balancing possible secondary traumatization exposure when discussing student ACEs, school counselors are at risk for experiencing trauma-related burnout (Rumsey et al, 2020). Experts strongly encourage practitioners to buffer the personal impact of working with trauma survivors by developing a self-care plan that includes peer support, supervision, consultation, training, individual therapy, and setting clear boundaries with students/clients (SAMHSA, 2014b).…”
Section: Trauma and School Counselorsmentioning
confidence: 99%